Isolation and restriction endonuclease (RE) site characterization of human 20-KDA myosin light chain 2 (MLC-2) gene from human colorectal system - Chia, Christine Pek Imm (Universiti Malaysia Sarawak, UNIMAS, 2007)
Colorectal cancer progresses in a stepwise manner and is found to be linked with the accumulating mutations (Franks and Teich, 1993). The recent discovery found that the expression of human 20-kDa Myosin Light Chain (MLC-2) gene is downregulated in the tumour colon tissue compared to the normal colon tissue (Sim et al., 2006). The objective of this study is to screen for mutation in the MLC-2 gene of the normal and tumour samples by restriction endonucleases. Total RNA of both samples was used as the starting material and was transcribed into cDNA using M-MLV reverse transcriptase. The 251 bp MLC-2 gene was successfully amplified by polymerase chain reaction and was subsequently digested with 15 different restriction endonucleases. The digestion yielded no abnormal cleavage of the MLC-2 gene fragment between tumour and normal colon samples.